Simulation Model of Divided Wall Distillation Column (DWDC) - Ahmed Hussien (Misan Journal of Engineering Sciences)
Abstract: Separating three high-purity products from a mixture of three components requires a series of columns for distillation and separation. This process results in significant operational and capital costs, as well as a substantial footprint within the plant. To address these issues, a type of distillation column referred to as a Divided Wall Distillation Column (DWDC) has been recently designed. This design incorporates a wall within the conventional distillation column, effectively partitioning the column into four distinct sections: Top, Bottom, Main fractionation, and Prefractionation. This distillation column effectively separates three components, and in some instances, four components, within a single unit. This design minimizes total costs, reduces operating expenses, and occupies less space within the facility. However, this type of distillation column (DWDC) is not represented in any of the simulation software utilized for distillation column simulations, including gPROMS ®, ASPEN Pulse ®, and HYSYS ®, among others. In this research, we developed several models that simulate the operation of (DWDC), achieving favorable verification results between the practical values and the simulation values.